Efficacy of a colostrum substitute on passive immunity transfer in calves - Elizondo-Salazar, Jorge Alberto (2021)
Introduction. Colostrum substitutes have increased in popularity in Costa Rica as an alternative to poor quality colostrum, limited colostrum reserves, or to break the cycle of transmission of certain infectious diseases. However, it is important to make sure that these products are effective and capable of providing adequate serum IgG concentration. Objective. To evaluate the efficacy of a colostrum substitute versus maternal colostrum in dairy heifer calves. Materials and methods. The experiment was carried out during the first semester of 2019 in sixty Jersey calves (twenty calves per treatment) that were randomly assigned to 1 of 3 treatment groups that consisted of supplementing the calves with: 3 l of maternal colostrum (group 1), 335 g of a colostrum replacer product containing 150 g of IgG (group 2), and 2 l of maternal colostrum + 110 g of colostrum supplement containing 55 g of IgG (group 3). Blood samples from all calves were collected 48 h after colostrum administration and analyzed for total serum protein and IgG concentration. Results. Calves fed maternal colostrum and maternal colostrum + colostrum supplement had significantly higher (p<0.05) total serum protein and IgG concentration compared to calves fed the colostrum substitute product; however, calves that received the colostrum replacer achieved an adequate passive transfer of immunity (> 10 g of IgG) and had a higher apparent efficiency of absorption. There were no significant differences (p>0.05) on calf growth parameters and health status of the calves. Conclusions. The evaluated colostrum replacer product provided an adequate IgG concentration in the assessed Jersey heifer calves and could be used as an alternative when there is no maternal colostrum.